The prognostic significance of admission blood glucose levels in patients with urinary tract infection. (May 2016) - Akirov, Amit; Elis, Avishay
Highlights: Blood glucose levels on admission are readily available for hospitalized patients. The first study to evaluate ABG and short- and long-term outcomes following UTI. There is a significant association between ABG and mortality in patients without DM. In DM patients there was no association between ABG and risk of all-cause mortality. Abstract: Aims: Evaluate the association between admission blood glucose (ABG) and short and long-term outcomes following hospitalization for urinary tract infection (UTI). Methods: Single center, retrospective cohort study of patients admitted to medical wards between January 1, 2011 and December 31, 2013 with a diagnosis of UTI. Patients were classified to those with diabetes mellitus (DM) and those without it. ABG levels were classified to categories: ≤70, 70–110, 111–199, ≥200 mg/dl. Primary outcome was all-cause mortality within 30-days and 1-year. Secondary outcomes were hospital readmissions within 30-days and 1-year, and survival rates at end of follow-up. Results: Cohort included 3405 patients (median age, 78 years; 44% men), 1106 with DM and 2299 without it. Among patients without DM, compared with ABG between 70 and 110 mg/dl ( n = 852, 37%), there was a significant association between ABG and all-cause mortality: hazard ratios (95% CI) with ABG ≤70 mg/dl ( n = 13, 0.6%), 111–199 mg/dl ( n = 1292, 56%), and ≥200 mg/dl ( n = 142, 6%) were: 3.67 (0.89–15.14, p = 0.07, 23% mortality ( n = 3)), 1.85 (1.29–2.64, p < 0.001, 7% mortality ( n = 89)), and 2.94 (1.71–5.07, p < 0.0001, 11% mortality ( n = 15)) at 30-days, and 3.8 (1.87–7.71, 38% mortality ( n = 5)), 1.35 (1 1.13–1.60, 7% mortality ( n = 215)), and 2.02 (1.50–2.71, 25% mortality ( n = 35)) at 1-year (all p < 0.001). In patients with DM there was no significant association between ABG and mortality. There was no association between ABG and readmissions in both groups. Conclusion: There is a significant association between ABG and short and long-term, all-cause mortality in patients without DM, but not in patients with DM, hospitalized for UTI.